(untitled) (Talenta Conference Series: Science and Technology (ST), 2019)
Makalah ini membahas Kalman filter dan Persamaan Aljabar Ricatti (PAR) untuk waktu diskrit. Lebih lanjut, sistem deskriptor varian waktu ditampilkan dalm bentuk formulasi umum. Pendekatan deterministik digunakan untuk menentukan bentuk optimum menjadi formulasi 9-block. Pernyataan 9-block selain menyatakan tahapan kondisi ruang, juga menampilkan struktur sederhana yang menarik dan simetris. Kemudian, kami akan menunjukkan bahwa Persamaan Aljabar Ricatti (PAR) memiliki semidefinit dan menstabilkan sistem. In this paper will discuss the Kalman filter and Riccati equation for discrete-time. Furthermore, time-variant descriptor systems presented in a common formulation. Deterministic approach used to determine the optimal form into the formulation "9-block". The expression "9-block", besides stating stages pending state space, also presents a simple structure that is interesting and symmetrical. And then, we will show that the Aljabar Riccati Eqution has a stabilizing semi-definit.